Clinical review: Early patient mobilization in the ICU - Hodgson, C.; Berney, S.; Harrold, Megan; Saxena, M.; Bellomo, R. (Australasian Academy of Critical Care Medicine, 2013)
Early mobilization (EM) of ICU patients is a physiologically logical intervention to attenuate critical illness-associated muscle weakness. However, its long-term value remains controversial. We performed a detailed analytical review of the literature using multiple relevant key terms in order to provide a comprehensive assessment of current knowledge on EM in critically ill patients. We found that the term EM remains undefined and encompasses a range of heterogeneous interventions that have been used alone or in combination. Nonetheless, several studies suggest that different forms of EM may be both safe and feasible in ICU patients, including those receiving mechanical ventilation. Unfortunately, these studies of EM are mostly single center in design, have limited external validity and have highly variable control treatments. In addition, new technology to facilitate EM such as cycle ergometry, transcutaneous electrical muscle stimulation and video therapy are increasingly being used to achieve such EM despite limited evidence of efficacy. We conclude that although preliminary low-level evidence suggests that EM in the ICU is safe, feasible and may yield clinical benefits, EM is also labor-intensive and requires appropriate staffing models and equipment. More research is thus required to identify current standard practice, optimal EM techniques and appropriate outcome measures before EM can be introduced into the routine care of critically ill patients.